Growth of Beaks in Layers Following Re-trimming - Glatz, P.C. (International Journal of Poultry Science, 2002)
Two experiments were conducted with 14 week-old pullets to examine whether severity of hot blade re-trimming and cauterisation time affected re-growth of beaks up to 30 weeks. In both experiments block cuts of the beak were made such that 5, 6 and 7 mm of the upper beak remained from the outer edge of the nostril to the end of the beak with a 2 mm step to the lower beak. A cauterisation time of 2 and 3 seconds was used in the first and second experiment respectively. Upper beak length at 30 weeks for layers in experiment 1 was not significantly different (p>0.05) between the treatments with upper beaks re-growing to 8.3, 8.7 and 9.1 mm respectively for the 5, 6 and 7 mm treatments. Similarly there was no difference in the length of the step at 14, 18 or 30 weeks of age. However, in the second experiment, the length of upper beaks (cut to 5, 6 and 7 mm at 14 weeks) were significantly different (p<0.05) at 30 weeks and only re-grew to 6.8, 7.9 and 8.9 mm respectively. Likewise a significant difference (p<0.05) in the length of the beak step was maintained up to 30 weeks. It is considered that the increase in the cauterisation time used for pullets in second experiment prevented substantial beak re-growth, especially for the severe levels of trimming.